2017
DOI: 10.1002/joc.5072
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of climate change on rice productivity in the Indochinese Peninsula using a regional‐scale crop model

Abstract: In order to assess the impact of climate change on rice yields for the Indochina peninsula region, a regional rice model was forced with climate variables from CORDEX‐East Asia climate models. The future climate's impact on rice yield varies between countries, and it is dependent on both current climate conditions and the projected future climate. Climate change alone would lead to a 3.5–23.2% and 5.8–27.2% reduction in rice yield for the 2020s and 2040s, respectively, in the Indochinese peninsula, with the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…WWF (1980) highlighted several immense ecological benefits of sagu: the palm is easily regenerated, requires no pesticide input, and provides food sources and habitat corridors for multiple species (Figure 10). Given observations of changes in rice season and harvest yields due to climate-related effects (Li et al 2017), existing ecosystems already achieving efficient staple food production like Siberut's sagu swamps and pumonean are vital in ensuring food security for a growing population, and have considerable value toward current biodiversity conservation efforts (World Resources Institute 2019). Considering the interconnectedness of culture and biodiversity (Posey 1999, Pretty et al 2009, those plants most valuable to a community, and the cultural traditions that ensue, are fundamental for biodiversity conservation and ecosystem regeneration.…”
Section: The Biological and Cultural Importance Of Sagumentioning
confidence: 99%
“…WWF (1980) highlighted several immense ecological benefits of sagu: the palm is easily regenerated, requires no pesticide input, and provides food sources and habitat corridors for multiple species (Figure 10). Given observations of changes in rice season and harvest yields due to climate-related effects (Li et al 2017), existing ecosystems already achieving efficient staple food production like Siberut's sagu swamps and pumonean are vital in ensuring food security for a growing population, and have considerable value toward current biodiversity conservation efforts (World Resources Institute 2019). Considering the interconnectedness of culture and biodiversity (Posey 1999, Pretty et al 2009, those plants most valuable to a community, and the cultural traditions that ensue, are fundamental for biodiversity conservation and ecosystem regeneration.…”
Section: The Biological and Cultural Importance Of Sagumentioning
confidence: 99%
“…The results of this study are supported by previous studies. Li et al [68] found that the predicted temperature contributed to approximately 59.7% of the uncertainty in rice yield projections. Krishnan et al [69] predicted changes of −9.02%, −11.3%, and −21.35% in rice yields with future climate projections generated from the GFDL, GISS, and UKMO scenarios, respectively.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Additionally, the FAO digital soil map of the world [57] was used for the dominant agricultural soil texture types. More detailed information on these data can be found in Li et al [58].…”
Section: Study Location and Data Collectionmentioning
confidence: 99%
“…The GLAM-Rice model is a regional-scale crop model that was used to project the impact of climate change on rice yields in Cambodia. More detailed information on the GLAM-Rice model and the calibration and validation methods for the model can be found in Li et al [58]. The model was forced by different climate change scenarios: the baseline (1991-2000) and 2030s (2021-2030) under two emission scenarios (typically, RCP 4.5 and RCP 8.5) from HadGEM3, YSU-RSM and RegCM4.…”
Section: Glam-rice Modelmentioning
confidence: 99%